L' Indépendant de Gand. (Gand : A. Boterdaele, 1896)
Redactie: J. Van den Heuvel, A. Boterdaele, A. DutryBeheer/Administratie: Grand Toquet 11, GandDrukker/Drukkerij: Imp. A. Boterdaele, Grand Toquet, Gand
Periodiciteit: dagelijksEerste nr.: 1 jan 1895Laatste nr.: 31 mei 1902
Frans
Krant
Keywords: katholieke pers; Gent